Princípio da precaução - aspectos controvertidos e desafios para a sua aplicação numa sociedade de risco - Patti Junior, Elcio (2007)
The industrialization and utilization of technology by our society in its present form of production are associated to a production process of environmental risk, which is many times undetected by society. The challenge presented to society is to find harmony between the pressures of those who search for economic growth and those who search for environmental protection. The Precautionary Principle appears as one of the main instruments in dealing with technological risks and their relations with environmental questions. However, the rapid diffusion and aplication of this principal in this society of risk, compel its proponents a clear demonstration of the importance of precaution in making environmental decisions. The decision makers must consider the evaluation of the potential consequences of omission, of the uncertanties and of the a scientific evaluation, when taking an action based on precaution. The present has the objective of debating questions that rouse concerning the application of the related principle, its relation with science and the technology a society of risk, considering the diversity of legal system and written laws, as well as the peculiar characteristics that are attributed to it by the legal doctrine and by the legal precedents in the national and international scenery